Speech acquisition predicts regions of enhanced cortical response to auditory stimulation in autism spectrum individuals. (September 2015) - Samson, F.; Zeffiro, T.A.; Doyon, J.; Benali, H.; Mottron, L.
Abstract: A continuum of phenotypes makes up the autism spectrum (AS). In particular, individuals show large differences in language acquisition, ranging from precocious speech to severe speech onset delay. However, the neurological origin of this heterogeneity remains unknown. Here, we sought to determine whether AS individuals differing in speech acquisition show different cortical responses to auditory stimulation and morphometric brain differences. Whole-brain activity following exposure to non-social sounds was investigated. Individuals in the AS were classified according to the presence or absence of Speech Onset Delay (AS-SOD and AS-NoSOD, respectively) and were compared with IQ-matched typically developing individuals (TYP). AS-NoSOD participants displayed greater task-related activity than TYP in the inferior frontal gyrus and peri-auditory middle and superior temporal gyri, which are associated with language processing. Conversely, the AS-SOD group only showed enhanced activity in the vicinity of the auditory cortex. We detected no differences in brain structure between groups. This is the first study to demonstrate the existence of differences in functional brain activity between AS individuals divided according to their pattern of speech development. These findings support the Trigger-threshold-target model and indicate that the occurrence of speech onset delay in AS individuals depends on the location of cortical functional reallocation, which favors perception in AS-SOD and language in AS-NoSOD. Highlights: We examined auditory processing in autism spectrum individuals with and without speech onset delay. Processing auditory information is associated with activity in auditory cortex in individuals with speech delay. Processing auditory information is associated with activity in language-related regions in individuals with no speech delay.